2014
DOI: 10.1186/s12967-014-0250-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphodiesterase 5 restores endothelial function in renovascular hypertension

Abstract: BackgroundThe clipping of an artery supplying one of the two kidneys (2K1C) activates the renin-angiotensin (Ang) system (RAS), resulting in hypertension and endothelial dysfunction. Recently, we demonstrated the intrarenal beneficial effects of sildenafil on the high levels of Ang II and reactive oxygen species (ROS) and on high blood pressure (BP) in 2K1C mice. Thus, in the present study, we tested the hypothesis that sildenafil improves endothelial function in hypertensive 2K1C mice by improving the NO/ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 64 publications
(84 reference statements)
2
20
0
1
Order By: Relevance
“…Interestingly, although some recent studies demonstrated that association with antioxidants (e.g., polyphenols or vitamin E) potentiates vascular protection [213,214], sildenafil may also provide intrinsic antioxidant effects through NADPH oxidase activity inhibition [215]. This evidence was complemented by our research in various models of hypertension, nephropathy or atherosclerosis and demonstrated protective effects for endothelial, cardiac and kidney functions in physiological parameters, such as morphological analyses (Figure 1) [209,212,216,217,218,219]. Therefore, our studies and other experimental evidence support the clinical findings of improvement in endothelial function, reduction of markers of vascular inflammation, and beneficial effects for conditions beyond erectile dysfunction [220,221,222,223,224].…”
Section: Beneficial Effects Of Phosphodiesterase Inhibitors In Diasupporting
confidence: 60%
“…Interestingly, although some recent studies demonstrated that association with antioxidants (e.g., polyphenols or vitamin E) potentiates vascular protection [213,214], sildenafil may also provide intrinsic antioxidant effects through NADPH oxidase activity inhibition [215]. This evidence was complemented by our research in various models of hypertension, nephropathy or atherosclerosis and demonstrated protective effects for endothelial, cardiac and kidney functions in physiological parameters, such as morphological analyses (Figure 1) [209,212,216,217,218,219]. Therefore, our studies and other experimental evidence support the clinical findings of improvement in endothelial function, reduction of markers of vascular inflammation, and beneficial effects for conditions beyond erectile dysfunction [220,221,222,223,224].…”
Section: Beneficial Effects Of Phosphodiesterase Inhibitors In Diasupporting
confidence: 60%
“…To our knowledge, we are the first to use flow cytometry to show that chronic sildenafil treatment by oral gavage, in addition to its vasoactivity, indirectly prevents damage to bone marrow cells by reducing ROS production and genomic instability which, consequently, preserves cell cycle kinetics in different cell types from atherosclerotic and hypertensive mice [7,10,[12][13][14]. Considering that the bone marrow is the primary stem cell source in adults and that autologous transplantation is the preferred therapy in clinical applications, our data provide insights into therapeutic potential of bone marrow stem cells from patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the mechanisms underlying atherosclerosis development and progression and how it impacts cell function, we use apolipoprotein E deficient (apoE −/− ) mice [1][2][3]11], which show high levels of plasma cholesterol and develop atherosclerotic lesions that resemble human disease. Emerging evidence suggests the beneficial effects of phosphodiesterase 5 (PDE5) inhibition with sildenafil on cardiovascular diseases and other target organs [6,7,10,[12][13][14]. However, the effects of sildenafil on oxidative DNA damage in bone marrow cells from apoE −/− mice have yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, recombinant human ACE2 treatment was able to rescue Ang II-mediated pathological actions in the ApoEKO mice with improvement of renal inflammation, oxidative stress and ultrastructure injury. ACE2 has local physiological effects, especially in the kidney, turning the balance within the RAS cascade from pro-inflammatory and pro-oxidant effects to anti-inflammatory and anti-oxidant effects [ 23 25 ]. Our data showed that downregulation of renal ACE2 levels was observed in the ApoEKO mice with no changes in SBP and renal Ang II levels.…”
Section: Discussionmentioning
confidence: 99%